Strategi Komunikasi Digital Komunitas Pencak Silat Indonesia dalam Membangun Identitas Budaya - M. Syafril Marib Setiawan Lebba; Drina Istyaswati; Priyono Sadjijo (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
This study aims to examine the digital communication strategies used by the Indonesian pencak silat community on social media platforms to enhance cultural imagery and encourage participatory engagement. The study seeks to understand how the community uses content, narratives, and interactions to maintain cultural identity while expanding its reach among younger audiences. Using a qualitative descriptive approach, data were collected through netnographic observation of social media activity on Instagram, TikTok, and YouTube, combined with in-depth interviews with key community members and followers. The results reveal that visual storytelling, hashtag campaigns, and interactive challenges are effective tools for cultural preservation and engagement. In addition, the community strategically positions silat not only as a martial art but also as a symbol of national identity. The study highlights how digital platforms can be participatory spaces that empower local traditions. The findings contribute to the discourse on digital cultural communication and offer practical insights for cultural communities seeking wider recognition in the digital era.